DYNAMIC SIMULATION FOR TRANSMISSION SYSTEM OF COAL WINNING MACHINE HAULAGE PART BASED ON RECURDYN SOFTWARE - PU ZhiXin; ZHOU ShuYe; DING DanDan (Jixie qiangdu)
To establish a rigid modle and a rigid-flexible coupling model of the transmission system of a coal winning machine haulage part,based on the theory of non-linear contact theory and multi-body dynamic. Applying ANSYS software to the rigid gear of flexible,and importing the model into the multi-body dynamics software RecurDyn for simulation analysis. The gear meshing process was described intuitively and dynamically under the simulation animation environment,and according to the simulation results to optimize the transmission system. The comparison of the simulation results of the rigid modle and a rigidflexible coupling model showed that the dynamic performance of rigid-flexible coupling model is more consistent with the actual.The problems of a large mechanical transmission mechanism’s multi-body contact simulation were solved,the theory laid the foundation for the applications of gear multi-body dynamics model in engineering.